2020
DOI: 10.1177/0363546520919120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Results of Arthroscopic Rotator Cuff Repair: A Follow-up Study Comparing Single-Row Versus Double-Row Fixation Techniques

Abstract: Background: Arthroscopic rotator cuff repair (RCR) with suture anchor–based fixation techniques has replaced former open and mini-open approaches. Nevertheless, long-term studies are scarce, and lack of knowledge exists about whether single-row (SR) or double-row (DR) methods are superior in clinical and anatomic results. Purpose: To analyze long-term results after arthroscopic RCR in patients with symptomatic rotator cuff tears and to compare functional and radiographic outcomes between SR and DR repair techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 33 publications
2
42
0
4
Order By: Relevance
“…MRI was obtained at the 2-year follow-up and revealed full-thickness retears in 6 of 22 patients (27%) who did not undergo revision, while 9 of 20 patients (45%) had full retears at 12 years postoperatively. When compared with the current study, Plachel et al's 15 group has fewer patients (11 vs 69) but a similar follow-up time and technique. Their revision rate was also higher (9.1% vs 5.5%) than in the current study, but the small sample size also makes this comparison difficult.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…MRI was obtained at the 2-year follow-up and revealed full-thickness retears in 6 of 22 patients (27%) who did not undergo revision, while 9 of 20 patients (45%) had full retears at 12 years postoperatively. When compared with the current study, Plachel et al's 15 group has fewer patients (11 vs 69) but a similar follow-up time and technique. Their revision rate was also higher (9.1% vs 5.5%) than in the current study, but the small sample size also makes this comparison difficult.…”
Section: Discussionmentioning
confidence: 50%
“…This value is much lower than in previously documented literature on rotator cuff repair. 8,9,15,16 These results are quite promising, although there were no long-term structural data. It is possible that there were patients in our cohort with minimally symptomatic or asymptomatic retears that did not require further surgery; however, the long-term nature of the study makes these types of failure less significant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…When comparing various techniques in the clinical setting, there have been at least 11 studies that have directly compared single-vs. double-row techniques for clinical and functional outcomes. 3,21,26,41,42,46,60,62,66,78,84 Of these studies, 8 of 11 showed no difference between single-and double-row repairs. Two studies 66,78 noted differences between groups, but these were for large tears (>3cm) only.…”
Section: Suture Techniquesmentioning
confidence: 99%
“…Regarding studies that specifically compared double-vs. singlerow repair for healing rates of RCR, 5 of 8 found no difference in healing. 21,41,60,66,84 For the 3 studies that did demonstrate a difference, 26,42,62 all favored the double-row construct. Gartsman 42 in a comparative study of 83 patients at 10 months found double-row suture bridge repair rates of failure at 7% which was significantly lower than the 25% rate of his single-row repairs with simple sutures.…”
Section: Suture Techniquesmentioning
confidence: 99%